1998
DOI: 10.1111/j.1600-0447.1998.tb10116.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of bipolar disorder in children and adolescents from India

Abstract: Bipolar disorder in adults is known to run an episodic course. However, little information exists on the long-term naturalistic course of bipolar disorder in juvenile populations. The present study was undertaken with the objectives of (i) documenting the rates of recovery and relapse, (ii) identifying the predictors of recovery and relapse and (iii) assessing the rates of comorbid conditions. A total of 30 subjects with onset of bipolar illness (according to DSM-III-R criteria) in childhood and adolescence we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 15 publications
8
57
1
Order By: Relevance
“…First, previous studies have not reported information regarding medication adherence, despite the strong association between treatment adherence and high recovery rates in studies of bipolar adults (12). Second, although most outcome studies of bipolar youth include a subset of adolescents close to their illness onset (3)(4)(5)(6)(7)(8)(9)(10)(11), no study, to our knowledge, has examined the outcome exclusively of adolescents hospitalized for their first manic episode. Studying patients early in their illness course permits identification of factors associated with recovery that may be difficult to detect in patients who have had multiple affective episodes, where illness chronicity may become the most significant predictor of outcome (3,12,13).…”
Section: (Am J Psychiatry 2007; 164:582-590)mentioning
confidence: 88%
See 1 more Smart Citation
“…First, previous studies have not reported information regarding medication adherence, despite the strong association between treatment adherence and high recovery rates in studies of bipolar adults (12). Second, although most outcome studies of bipolar youth include a subset of adolescents close to their illness onset (3)(4)(5)(6)(7)(8)(9)(10)(11), no study, to our knowledge, has examined the outcome exclusively of adolescents hospitalized for their first manic episode. Studying patients early in their illness course permits identification of factors associated with recovery that may be difficult to detect in patients who have had multiple affective episodes, where illness chronicity may become the most significant predictor of outcome (3,12,13).…”
Section: (Am J Psychiatry 2007; 164:582-590)mentioning
confidence: 88%
“…Al though the onset of bipolar disorder most commonly occurs during adolescence (1,2), there have been relatively few naturalistic outcome studies of children and adolescents with bipolar disorder (3)(4)(5)(6)(7)(8)(9)(10)(11). Prospective studies of clinical cohorts of bipolar youth have reported recovery and recurrence rates that range from 14%-100% and 35%-70%, respectively, during follow-up periods of 6 months to 4 years.…”
Section: (Am J Psychiatry 2007; 164:582-590)mentioning
confidence: 94%
“…(Am J Psychiatry 2007; 164: [582][583][584][585][586][587][588][589][590] Al though the onset of bipolar disorder most commonly occurs during adolescence (1,2), there have been relatively few naturalistic outcome studies of children and adolescents with bipolar disorder (3)(4)(5)(6)(7)(8)(9)(10)(11). Prospective studies of clinical cohorts of bipolar youth have reported recovery and recurrence rates that range from 14%-100% and 35%-70%, respectively, during follow-up periods of 6 months to 4 years.…”
mentioning
confidence: 99%
“…Furthermore, reports from two longitudinal studies support significant mortality from suicide among pediatric BP patients. Srinath et al (8) reported a 3% suicide rate among pediatric BPI patients 5 years after index episode hospitalization, whereas Welner et al (9) documented a 25% suicide completion rate among a BP adolescent inpatient sample (when compared with 6% among unipolar patients) at 10-year follow up.…”
mentioning
confidence: 99%